(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
In this work, Silk Fibroin (SF) nanofibers were electrospun onto plasma-treated 100% cotton gauze bandages to form a novel silk-gauze composite wound dressing. Atmospheric pressure plasma pre- and post-treatments were used to increase the adhesion between the SF nanofibers and cotton substrates. The adhesion of the nanofibers to the substrates was assessed by qualitative and quantitative techniques. Plasma pre-treatment of the substrate with 100% helium and 99% helium/1% oxygen plasmas showed up to a 50% increase in the force required to peel off the nanofiber layer. This force was further increased up to 75% after pre- as well as post-plasma treatment of the composite bandages. Plasma pre-treatment of the gauze fabric prior to nanofiber deposition and post-treatment to the composite bandages significantly reduced degradation of the nanofiber layer during repetitive flexing. Air permeability and moisture vapor transport were significantly reduced due to the presence of a nanofiber layer upon the substrate. The results of surface elemental analysis showed that the adhesion and durability increase are mainly due to the active species generated by plasma on the surface of cotton substrate as well as on the surface of the silk fibroin nanofibers.